2017
DOI: 10.1017/s0266462317001052
|View full text |Cite
|
Sign up to set email alerts
|

Inahta Impact Story: Legislative and Accreditation Requirements for Office-Based Surgery in Australia

Abstract: The legislative and accreditation framework creates a situation whereby healthcare facilities that provide services outside the various legal definitions of surgery and those not covered by a reimbursement scheme, can operate without licensing and accreditation oversight. This situation exposes patients to potential increased risk of harm when receiving treatment in such unregulated facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Various professional colleges have called for quality assurance processes to be instituted in all surgical areas of OBA 27 . In a recent review article examining the regulations for office-based procedures, it was determined that currently there were no national safety and quality service standards for office-based facilities encompassing the provision of surgical and anaesthetic care 28 . The authors found that this situation exposes patients to potential increased risk of harm when receiving treatment in such unregulated facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Various professional colleges have called for quality assurance processes to be instituted in all surgical areas of OBA 27 . In a recent review article examining the regulations for office-based procedures, it was determined that currently there were no national safety and quality service standards for office-based facilities encompassing the provision of surgical and anaesthetic care 28 . The authors found that this situation exposes patients to potential increased risk of harm when receiving treatment in such unregulated facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Their story brings to light the role that organizational culture can have in the transfer and application of new knowledge in clinical practice. From the Australian Safety and Efficacy Register of New Interventional Procedures-Surgical (ASERNIP-S) comes a story by Tivey et al (12) about their application of rapid review HTA methods to assess the legislative and accreditation requirements for office-based surgery in Australia. Their results show that loopholes exist where higher-risk surgeries could occur without the necessary clinical practice safeguards.…”
mentioning
confidence: 99%